140 million years of evolutionary history without wings: Phylogeny and biogeography of cave crickets (Orthoptera: Rhaphidophoridae) ... - Kim, Do-Yoon; Kim, Sangil; Song, Hojun; Shin, Seunggwan (Zenodo, 2024)
The family Rhaphidophoridae is an ancient and wingless lineage within Orthoptera that shows a worldwide distribution except Antarctica, with a high level of endemicity for each subfamily. Nevertheless, the phylogenetic relationships within the family remain poorly resolved due to its morphological uniformity and lack of diagnostic characteristics, such as wings. To clarify the systematics of Rhaphidophoridae and its biogeographic history, a molecular phylogeny of Rhaphidophoridae was reconstructed using three mitochondrial genes (COI, 12S, and 16S) and two nuclear ribosomal RNA genes (18S and 28S). We proposed the most comprehensive phylogenetic hypothesis of the family to date, including all extant subfamilies for the first time. In particular, we included the representatives of Anoplophilinae from East Asia to propose its phylogenetic placement for the first time, and we also included the members of Tropidischinae and Gammarotettiginae from the western United States. We resolved phylogenetic relationships ...